1997
DOI: 10.1159/000127214
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Insulin-Like Growth Factor Binding Protein-2 during Postnatal Development of the Rat Neurointermediate Pituitary

Abstract: The expression of insulin-like growth factor binding protein-2 (IGFBP-2) during postnatal development of the rat neurointermediate pituitary was characterized using immunocytochemistry and in situ hybridization. Glial cells in the neural lobe (NL) showed robust expression of IGFBP-2 throughout the postnatal period and continuing into adulthood. These were identified as pituicytes by the presence of S-100 protein; IGFBP-2 was not present in microglia in the NL. IGFBP-2 immunoreactivity was more punctate in matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
2
1
Order By: Relevance
“…As demonstrated in Figure 3G, no colocalization was evident when binding of OX-42 (red, CY-3) was localized simultaneously with anti-hrIL-1␤ (green, FITC) using confocal microscopy. Similar results were obtained when binding of antisera to S100, an astrocytespecific Ca ϩϩ -binding protein (Cocchia and Miana, 1980;Zhou et al, 1997), was colocalized with binding of antihrIL-1␤. As illustrated in Figure 3H, no colocalization of S100-ir (red, CY-3) and anti-IL-1␤-ir (green, FITC) was evident.…”
Section: Il-1␤ Immunoreactivity Does Not Colocalize With Pituicytes Osupporting
confidence: 78%
“…As demonstrated in Figure 3G, no colocalization was evident when binding of OX-42 (red, CY-3) was localized simultaneously with anti-hrIL-1␤ (green, FITC) using confocal microscopy. Similar results were obtained when binding of antisera to S100, an astrocytespecific Ca ϩϩ -binding protein (Cocchia and Miana, 1980;Zhou et al, 1997), was colocalized with binding of antihrIL-1␤. As illustrated in Figure 3H, no colocalization of S100-ir (red, CY-3) and anti-IL-1␤-ir (green, FITC) was evident.…”
Section: Il-1␤ Immunoreactivity Does Not Colocalize With Pituicytes Osupporting
confidence: 78%
“…Hypertrophic astrocytes at the lesion edges of MS plaques showed enhanced expression of IGFBP‐2 and IGFBP‐4. IGFBP‐2 is highly expressed in the CNS, and is the major IGFBP in cerebrospinal fluid (Kelly et al ., 1996; Zhou et al ., 1997). We have previously shown that reactive microglia and macrophages in MS lesions also display enhanced immunoreactivity for IGFBP‐2 (Chesik et al ., 2004a).…”
Section: Discussioncontrasting
confidence: 99%
“…In order to further define the cell type(s) expressing the p75 NTR , we performed dual confocal fluorescence localizations pairing anti-S100, an astrocyte-specific Ca 2+ -binding protein (Cocchia and Miana 1980;Zhou et al 1997), and p75 NTR in NL. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%